The role of GLP-1 receptor agonists in IBD-related surgery and IBD-related complications of inflammatory bowel disease among patients with metabolic comorbidities: a systematic review and meta-analysis - Mengqi Yang; Yujia Huo; Yujia Huo; Yujia Huo; Zhining Liu; Guannan Bai; Dongjun He; Lin Zhang; Lin Zhang; Lin Zhang (Frontiers in Medicine)
BackgroundGlucagon-like peptide-1 receptor agonists (GLP-1RAs) are widely used for type 2 diabetes and obesity, and emerging evidence suggests potential immunomodulatory effects. However, few studies have evaluated their role in inflammatory bowel disease (IBD), and no comprehensive clinical trials exist. This meta-analysis aimed to assess the association between GLP-1RA use and IBD-related surgeries and complications.MethodsA systematic literature search was conducted in PubMed, Embase, and Web of Science from inception to March 2025. Cohort studies comparing IBD patients treated with GLP-1RAs versus non-users were included. Two reviewers independently performed study selection and data extraction. Random-effects meta-analyses were performed using log-transformed effect sizes. Heterogeneity was assessed using I2 and τ2. Publication bias was evaluated through funnel plots, and certainty of evidence was graded using the GRADE framework.ResultsSix studies were included, providing eight effect estimates (two studies contributed two cohorts each). Three of the six included studies (50%) were non–peer-reviewed conference abstracts, which may affect interpretability. For IBD-related surgery (4 effect estimates), GLP-1RA use was significantly associated with lower risk (pooled estimate: 0.45; 95% CI: 0.35–0.59; I2 = 38.1%). For IBD-related complications (4 estimates), GLP-1RA use showed a non-significant trend toward benefit (estimate: 0.39; 95% CI: 0.15–1.03), with high heterogeneity (I2 = 98.9%). Sensitivity analysis supported robustness for surgery but revealed instability in complication outcomes. Funnel plots showed no publication bias for surgery, but asymmetry was noted for complications.ConclusionGLP-1RA use may reduce the risk of IBD-related surgery among IBD patients with metabolic comorbidities. Findings for IBD-related complications should be interpreted with caution due to substantial heterogeneity and the inclusion of abstract-only studies. Further prospective research is warranted.Systematic review registrationThis systematic review was prospectively registered with the International Prospective Register of Systematic Reviews (PROSPERO), under registration ID CRD420251015882. The full protocol is publicly accessible through the PROSPERO database at https://www.crd.york.ac.uk/prospero/. No amendments were made to the original protocol. Any changes arising during the peer-review process will be transparently documented in the final publication.